Санкт-Петербургские филологи-классики и Томский государственный университет - Леушина , Л. Т.; Фоминых, С.Ф. (Philologia Classica, 2007)
A survey of scholarly and teaching activities of St. Petersburg professors of classics and of the classicists graduating from St. Petersburg University and St. Petersburg Historic-philological Institute at the University of Tomsk in 20th century